Primary Menouria due to Congenital Urethrovaginal Fistula with Vaginal Agenesis - Razak, Lubna; Mohsin, Raheela (Nepal Journal of Obstetrics and Gynaecology, 2018)
Congenital Urethrovaginal fistula with vaginal agenesis is a rare variant of vaginal agenesis. It is difficult to diagnose, classify and treat because of late clinical presentation at menarche. Management is usually challenging, and it involves vaginal reconstruction. A 22 years female presented with cyclical menouria since age of 12 years. Clinical examination revealed the absence of a vagina with developed secondary sexual characters such as axillary and pubic hair, breast development. Abdominal USG showed normal uterus and ovaries, urinary bladder with left kidney. MRI revealed functioning left kidney along with vaginal agenesis and an abnormal communication between uterus and urethra. The surgical treatment consisted in repairing the urethrovaginal fistula and vaginoplasty. In this case, the diagnosis of congenital urethrovaginal fistula was delayed until adulthood because of vaginal agenesis. A concomitant surgery can be performed with good outcome.